On the Lomechusini fauna of the Palaearctic and Oriental regions. XXVI. New species, a new synonymy, and additional records (Coleoptera: Staphylinidae: Aleocharinae) - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2019)
Types and additional material of twelve genera of Lomechusini from the Palaearctic and Oriental regions are revised. In all, 24 species are described and/or illustrated, 21 of them new: Pella feldmanni spec. nov. (China: Sichuan) of the P. cognata group; Orphnebius fortesetosus spec. nov. (China: Sichuan) and O. taurus spec. nov. (Cambodia) of the O. hauseri group; Orphnebius (Deroleptus) morulus spec. nov. (South Vietnam), O. (D.) globulifer spec. nov. (Malaysia: Pahang), O. (D.) elevatus spec. nov. (Laos), and O. (D.) moruliflavus spec. nov. (Malaysia: Sabah) of the O. siwalikensis group; Keratodegnathus cornutus spec. nov. (Malaysia: Pahang); Amaurodera schmidti spec. nov. (East Nepal) of the A. silvana group; A. brevipennis spec. nov. (Malaysia: Sabah); A. atra spec. nov. (Philippines: Mindanao); Drusilla bispinosa spec. nov. (Malaysia: Pahang); D. shavrini spec. nov. (Philippines: Mindanao); D. penicillata spec. nov. (Philippines: Mindanao); D. spiniventris spec. nov. (Philippines: Mindanao); D. breviuter spec. nov. (Philippines: Mindanao); Pheidologitonetes biplicatus spec. nov. (China: Yunnan); Zyras (Zyras) conlectus spec. nov. (Myanmar); Z. (Z.) hetzeli spec. nov. (Taiwan); Z. (Z.) reductus spec. nov. (Philippines: Mindanao); Z. (Z.) shavrini spec. nov. (Philippines: Mindanao). The following synonymy is established: Drusilla obliqua (Bernhauer, 1916) = D. zyrasoides Dvořak, 1988, syn. nov. Additional records of 49 named species are reported, among them twelve first records from Greece (1), Lebanon (1), Israel (1), Jordan (1), Iran (1), Nepal (1), China (1), Taiwan (1), Laos (1), Cambodia (2), and Borneo (1). The distribution of Myrmoecia urartu (Iablokoff-Khnzorian, 1962) is mapped. Taxonomic acts Pella feldmanni spec. nov. – urn:lsid:zoobank.org:act:E98B0247-7020-4845-B7B3-7FB5946DCA24 Orphnebius fortesetosus spec. nov. – urn:lsid:zoobank.org:act:CEE40705-FCE7-47A3-859A-614E2D7ADCAC Orphnebius taurus spec. nov. – urn:lsid:zoobank.org:act:9C47DCE3-7D9A-4D71-8A4B-24036B41A66D Orphnebius morulus spec. nov. – urn:lsid:zoobank.org:act:DF080E64-CDBB-4BE4-A7CF-D71EA3A270AC Orphnebius globulifer spec. nov. – urn:lsid:zoobank.org:act:F2AB5418-A6A3-4125-AB1B-5B6C18EEF85E Orphnebius elevatus spec. nov. – urn:lsid:zoobank.org:act:839D7EBF-6AD4-420B-97A1-8448D1F5036B Orphnebius moruliflavus spec. nov. – urn:lsid:zoobank.org:act:57A6C5B3-7F8A-46BB-88B3-2213C17C91A8 Keratodegnathus cornutus spec. nov. – urn:lsid:zoobank.org:act:042656C4-9410-4A3A-9648-037977E13C0C Amaurodera schmidti spec. nov. – urn:lsid:zoobank.org:act:7ABC3A7D-5EA4-47C5-90A5-F8F451BF1914 Amaurodera brevipennis spec. nov. – urn:lsid:zoobank.org:act:5AB88702-0D52-4B1F-A7AA-0654B71DC14F Amaurodera atra spec. nov. – urn:lsid:zoobank.org:act:7D5CCE81-D9AF-4599-B7C0-AA4D6D0AD8C2 Drusilla bispinosa spec. nov. – urn:lsid:zoobank.org:act:A3E4F51F-809D-407F-9DE0-5655A67106AC Drusilla shavrini spec. nov. – urn:lsid:zoobank.org:act:7EF756D2-6CFE-4230-AAF4-298C3D1B76BE Drusilla penicillata spec. nov. – urn:lsid:zoobank.org:act:CAA17FAD-AE2A-496C-9D08-84D34358BDD5 Drusilla spiniventris spec. nov. – urn:lsid:zoobank.org:act:BB6FB0AD-90DC-457E-90A1-0534A8AE43D6 Drusilla breviuter spec. nov. – urn:lsid:zoobank.org:act:43EDA558-1DBF-4861-B73F-F292EF6169C5 Pheidologitonetes biplicatus spec. nov. – urn:lsid:zoobank.org:act:77CC7252-1567-4522-A89E-9B0D5E1C486A Zyras conlectus spec. nov. – urn:lsid:zoobank.org:act:EEF29D05-2E17-4205-805A-B8BFFAE0FE98 Zyras hetzeli spec. nov. – urn:lsid:zoobank.org:act:F00342B5-F2BF-461A-A84A-282D19159065 Zyras reductus spec. nov. – urn:lsid:zoobank.org:act:15761BF9-31AA-4B92-A7A5-8C3535DF876C Zyras shavrini spec. nov. – urn:lsid:zoobank.org:act:A7C7B14F-AA8A-47EB-AA6F-F7A7C2B040A4